2007
DOI: 10.1016/j.jmb.2006.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Mutational Studies of Mycobacterium tuberculosis recA Mini-inteins Suggest a Pivotal Role for a Highly Conserved Aspartate Residue

Abstract: The 440-amino acid Mtu recA intein consists of independent protein-splicing and endonuclease domains. Previously, removal of the central endonuclease domain of the intein, and selection for function, generated a 168-residue mini-intein, ΔI-SM, that had splicing activity similar to that of the full-length, wild-type protein. A D422G mutation (ΔI-CM) increased C-terminal cleavage activity. Using the I-SM mini-intein structure (presented here) as a guide, we previously generated a highly active 139-residue mini-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
153
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(160 citation statements)
references
References 41 publications
7
153
0
Order By: Relevance
“…The essential characteristics of class 3 inteins are (i) cleavage at the N-terminal splice junction in the absence of all class 1 and class 2 splice junction nucleophiles at A:1, G:7, and G:8; (ii) activation of the N-terminal splice junction by a block B motif that includes the conserved His (2,20). Class 1 and 2 inteins also have a hydrophobic residue at the B:12 position (8,11,21), including Trp, which suggests that this position is involved in hydrophobic packing in all classes of inteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential characteristics of class 3 inteins are (i) cleavage at the N-terminal splice junction in the absence of all class 1 and class 2 splice junction nucleophiles at A:1, G:7, and G:8; (ii) activation of the N-terminal splice junction by a block B motif that includes the conserved His (2,20). Class 1 and 2 inteins also have a hydrophobic residue at the B:12 position (8,11,21), including Trp, which suggests that this position is involved in hydrophobic packing in all classes of inteins.…”
Section: Discussionmentioning
confidence: 99%
“…3). In class 1 and 2 inteins, mutations at F:4 inhibit splicing because this residue assists reactions at one or both splice junctions, depending on the individual intein (2,8,13,(19)(20)(21). In class 3 inteins, Ala substitution for this residue blocks all N-terminal cleavage reactions, including BI formation.…”
Section: Splicing Of Wild-type Inteinsmentioning
confidence: 99%
“…We used the RecA intein as the model in this study because of the wealth of structural and functional information available for this intein (13)(14)(15) and because intein inhibitors isolated against the RecA intein are also active against the DnaB intein (16), which is required for viability. Furthermore, RecA is one of the proteins associated with M. tuberculosis drug resistance (17), and mutation of RecA causes sensitivity to DNA-damaging agents and increased susceptibility to metronidazole (18 It has been reported that the intein activity can be suppressed by Zn 2ϩ and Cu 2ϩ ions (19 -21).…”
mentioning
confidence: 99%
“…Functional studies also indicated that several other conserved residues in the M. tuberculosis RecA intein are required for protein splicing, including His-73 and His-439. Crystal structures suggest that these residues are close in space and form the active site core of the M. tuberculosis RecA intein (13). Because cysteine and histidine residues are favored sites for platinum(II) binding in proteins, we hypothesized that platinum(II) complexes would be particularly suited to intein inhibition.…”
mentioning
confidence: 99%
“…Even if a branched ester can form, as we believe we observed with the intein with a single Cys320Ala mutation, uncoupled C-terminal cleavage is still prevented. Perhaps Cys320 is required to properly coordinate the active site to promote Asn cyclization, as with the Asp at that position in the Mycobacterium tuberculosis RecA intein (15,16). Alternatively, the Cys320 could promote proper branched-ester formation, with Asn cyclization being coupled to splicing in the context of a branched ester, as with the Mycobacterium xenopi GyrA intein (4).…”
mentioning
confidence: 99%